Examining the Role of ChatGPT as a Learning tool in Promoting Students' English Language Learning Autonomy relevant to Kurikulum Merdeka Belajar - Ni Putu Oka Agustini (LP. Ma'arif Janggan Magetan, 2023)
This study aimed to examine the effect of ChatGPT, an AI-powered chatbot, as a learning aid in encouraging English language learning autonomy among Indonesian students enrolled in the Kurikulum Merdeka Belajar (KMB) program. The study used a mixed-methods research approach that included questionnaires and semi-structured interviews to examine how English Language Learners utilize ChatGPT to regulate their learning processes, establish objectives, and make decisions about their English language acquisition. Additionally, the study explored how ChatGPT can be integrated into the KMB program to promote autonomy and personalized learning. Previous studies have shown that technology can promote autonomy in language learning. However, there is a need for more research on the specific role of ChatGPT in promoting autonomy in language learning. The study will contribute to language teaching and learning by providing insights into how ChatGPT can promote autonomy and personalized learning among ELLs in the KMB program. It also provides practical recommendations for language teachers and policymakers on integrating ChatGPT into language learning programs to promote autonomy and personalized learning.